Non trivial frames for f(T) theories of gravity and beyond - Ferraro, Rafael (2011)
Some conceptual issues concerning f (T ) theories – a family of modified gravity theories based on absolute parallelism – are analyzed. Due to the lack of local Lorentz invariance, the autoparallel frames satisfying the field equations are evasive to an a priori physical understanding. We exemplify this point by working out the vierbein (tetrad) fields for closed and open Friedmann–Robertson–Walker cosmologies.